2021
DOI: 10.7759/cureus.19976
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety and Efficacy of Remdesivir Versus Remdesivir Plus Convalescent Plasma Therapy (CPT) and the Effect of Timing of Initiation of Remdesivir in COVID-19 Patients: An Observational Study From North East India

Abstract: IntroductionAs per the COVID-19 treatment guidelines of India, remdesivir and convalescent plasma therapy (CPT) are indicated in moderate and severe patients. In this study, we have evaluated the comparative safety and efficacy of remdesivir versus remdesivir CPT combination and effect of early versus late initiation of remdesivir. Materials and methodsA hospital-based observational study was conducted among hospitalized moderate and severe COVID-19 patients treated with either remdesivir and/or CPT as per nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…No major untoward effects related to Remdesivir were observed in this study. This is in contradiction to the previous studies, which reported other side effects, such as diarrhea and rash [ 49 , 50 ]. Remdesivir elevated the ALT levels mildly in three patients (3.61%) after three doses, but remained static after five doses.…”
Section: Discussioncontrasting
confidence: 99%
“…No major untoward effects related to Remdesivir were observed in this study. This is in contradiction to the previous studies, which reported other side effects, such as diarrhea and rash [ 49 , 50 ]. Remdesivir elevated the ALT levels mildly in three patients (3.61%) after three doses, but remained static after five doses.…”
Section: Discussioncontrasting
confidence: 99%
“…Liver and kidney toxicity may be due to the destruction of the lysosomal membrane caused by remdesivir leading to the liberation of their hydrolytic enzymes, which promote death and lysis of the cells (32). In the present study, distortion in the histological structure of the liver and kidneys could be due to the intermediate substances secreted by inflammatory cells, causing vasodilation and congestion of blood vessels (33).…”
Section: Discussionmentioning
confidence: 55%